Rodent diversity in South America: transitioning into the genomics era - Lessa, Enrique P.; Cook, Joseph A.; D'Elía, Guillermo; Opazo, Juan C. (Frontiers in Ecology and Evolution, 2014)
The goal of this perspective is to propose a concerted effort for the study of the diversity of South American rodents to transition into the genomic era. We first review progress made in the last few decades in our understanding of the age, geographical origins, phylogenetic relationships and diversity of caviomorph and sigmodontine rodents, two major components of the South American fauna. Then, we examine their current representation in genomic/transcriptomic databases, and outline a research program to obtain a set of genomes and transcriptomes that represent major groups within each of these two lineages. We propose standards for voucher specimens and associated data and explore the role of museums and research collections in this endeavor. We envision a concerted international effort to guide and accelerate progress in the field.